Pendekatan Pembelajaran Saintifik dalam Bahasa Arab - M. Dzikrul Hakim Al Ghozali (Menara Tebuireng, 2017)
Improving the quality of teaching and make learning becomes interesting is the task of educators. So here educators must be more creative in learning pack. One of the learning process that seeks to create a creative learning system is a scientific study. Scientific Learning is learning to adopt measures Santis in building of scientific knowledge. Learning is not just looking at the learning outcomes as the estuary end, but the learning process is deemed very important. This approach emphasizes the search process knowledge, with regard to learning materials through the kinds of activities: to observe, ask, try, associate and communicate and in its development of learning scientific can not only be applied to the field of science applied science (eksakta) but can be used also in all branches disciplines including Arabic